2012
DOI: 10.3109/14767058.2012.715011
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular distraction osteogenesis for neonates with Pierre Robin sequence and airway obstruction

Abstract: Neonates with Pierre Robin Sequence (PRS) usually present with varying degrees of upper airway obstruction and difficulty feeding. Early treatment is important for such children in order to prevent impaired cognitive development resulting from hypoxemic episodes. Various procedures aimed at widening the pharyngeal space have been proposed, including prone position, tongue-lip adhesion, mandibular traction, non-invasive ventilation and palatal plates. Mandibular distraction osteogenesis (MDO) using external or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…AHI measurement requires the use of polysomnography as an assessment tool for quantifying surgical outcomes, and is not consistently used across and within all studies (Denny, 2004;Schaefer et al, 2004;Dauria and Marsh, 2008;Cicchetti et al, 2012). Furthermore, the requirement of an improvement in AHI may identify patients who have avoided tracheostomy but still have a high degree of airway obstruction (AHI >5e10) and as a result, require major supplemental airway support such as continuous positive airway pressure (CPAP) or home oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…AHI measurement requires the use of polysomnography as an assessment tool for quantifying surgical outcomes, and is not consistently used across and within all studies (Denny, 2004;Schaefer et al, 2004;Dauria and Marsh, 2008;Cicchetti et al, 2012). Furthermore, the requirement of an improvement in AHI may identify patients who have avoided tracheostomy but still have a high degree of airway obstruction (AHI >5e10) and as a result, require major supplemental airway support such as continuous positive airway pressure (CPAP) or home oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…The T allele of MTHFR variant rs1801133 has been found to be associated with higher homocysteine levels (Jacques et al, 1996; Rozen, 1997; Yang et al, 2008), and increased homocysteine levels (and its metabolites) have been found to be associated with global DNA hypomethylation (Yi et al, 2000; Caudill et al, 2001). In addition, hypomethylation was observed in women carrying one minor T allele in conjunction with folate deficiency, and in women carrying two minor T alleles of MTHFR rs1801133 in the presence of vitamin B6 deficiency (Axume et al, 2007; La Merrill et al, 2012). Similarly, mice with one or both copies of MTHFR knocked out showed hyperhomocysteinemia as well as global DNA hypomethylation (Chen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…External devices are easier to adjust and remove, but can be dislodged, and are associated with scarring. Internal devices tend to be better tolerated, but may require repeat general anesthetics for adjustment and removal (101). Many centers have moved towards internal devices as recent developments have meant that anesthetics for adjustment may no longer be necessary (Figure 4).…”
Section: Treatment Of Osa In Children With Pierre Robin Sequencementioning
confidence: 99%